2022
DOI: 10.1080/07853890.2022.2061045
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium nucleatum induces MDSCs enrichment via activation the NLRP3 inflammosome in ESCC cells, leading to cisplatin resistance

Abstract: Background To analyse the regulatory effect of Fusobacterium nucleatum (Fn) on NOD-like receptor protein 3 (NLRP3) and myeloid-derived suppressor cells (MDSCs) in oesophageal squamous cell carcinoma (ESCC) as well as its effect on cisplatin (CDDP) therapy and to explore its clinical significance. Methods Fn infection, NLRP3 expression and MDSCs infiltration in ESCC tissues were detected by RNAscope and immunohistochemistry (IHC). The correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“… 22 Liang et al demonstrated recently that F. nucleatum increased the expression of NLRP3 followed by the enrichment of myeloid-derived suppressor cells, thereby leading to ESCC cell chemoresistance. 38 However, the underlying relationship between F. nucleatum and therapy-induced senescent ESCC cells to date remains unknown. In the present study, we observed that CDDP-induced senescent cells after co-cultured with F. nucleatum further exacerbated the SASP-driven ESCC cell proliferation, migration, invasion, and chemoresistance both in vitro and in vivo , suggesting the contribution of F. nucleatum to the secretion of the SASP by senescent cells.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Liang et al demonstrated recently that F. nucleatum increased the expression of NLRP3 followed by the enrichment of myeloid-derived suppressor cells, thereby leading to ESCC cell chemoresistance. 38 However, the underlying relationship between F. nucleatum and therapy-induced senescent ESCC cells to date remains unknown. In the present study, we observed that CDDP-induced senescent cells after co-cultured with F. nucleatum further exacerbated the SASP-driven ESCC cell proliferation, migration, invasion, and chemoresistance both in vitro and in vivo , suggesting the contribution of F. nucleatum to the secretion of the SASP by senescent cells.…”
Section: Discussionmentioning
confidence: 99%
“…50 Higher intratumoral F. nucleatum levels were related to lower chemotherapy response 60,63,64 and shortened survival in ESCC patients. 60 Based on the above literature, the abundance of P. gingivalis or F. nucleatum in the oral cavity and esophagus…”
Section: Fusobacterium Nucleatum and Esccmentioning
confidence: 98%
“…In a cell‐line study, Nomoto et al demonstrated that F. nucleatum promotes ESCC cell growth and migration by activating the NOD1/RIPK2/NF‐κB pathway 59 . Liang et al revealed F. nucleatum induces immunosuppressive myeloid‐derived suppressor cell (MDSC) enrichment via activation of the NOD‐like receptor protein 3 (NLRP3) inflammasome 60–62 . F. nucleatum can also induce chemoresistance in ESCC cells by modulating autophagy 63 .…”
Section: Dysbiosis In Esophageal Squamous Cell Carcinomamentioning
confidence: 99%
“…MDSCs exhibit an increased activation of NLRP3 during tumor development. Ablation of the NLRP3/pro-IL-1b inflammasome rewires MDSC function, promotes melanoma (112) and breast cancer (113) regression, and causes cisplatin resistance (114). NLRP3 inhibition and anti-PD-1 treatment significantly increased the antitumor efficacy of monotherapy by limiting MDSC-mediated T cell suppression and melanoma tumor progression (76).…”
Section: Inflammasome Signalingmentioning
confidence: 99%